Choroid plexus tumours: Classification, MR imaging findings and pathological correlation. Issue 2 (28th December 2012) - Yan, Chenggong; Xu, Yikai; Feng, Jie; Sun, Chongpeng; Zhang, Ge; Shi, Jie; Hao, Peng; Wu, Yuankui; Lin, Bingquan
Abstract Introduction Choroid plexus tumours (CPTs) are extremely rare intraventricular neoplasms and are prone to bleeding during surgery. The purpose of this study was to summarise the MR imaging characteristics of 13 CPT cases. Methods Magnetic resonance images of 13 patients (six men and seven women; mean age 21.1 years) with pathologically proved CPTs were retrospectively reviewed. MR findings of the tumours were evaluated, with emphasis on their location, size, shape, internal architecture, margin and pattern and degree of enhancement. Differences in signal intensity characteristics were also investigated on MR images and analysed according to histological subtypes. Results Lesions were in the lateral ventricles (n = 7), fourth ventricle (n = 5) and cisterna magna (n = 1), with a mean size of 5.0 cm (range 2.0–7.9 cm). The tumour parenchyma was a mixture of nodular or patchy areas of inhomogeneous isointense to slightly hyperintense signal on T2‐weighted images. On postcontrast MR images, all lesions, except for one, had moderate to marked contrast enhancement. Multiple tortuous areas of 'flow void' signal extended through all the tumours except for two. A thin capsule could be seen in six cases. Conclusion Observation of large intraventricular tumours with inhomogeneity on T2‐weighted images and flow void is suggestive of CPTs. Checking for signs of a thin capsule, extensive peritumoural oedema and necrosis may be useful when classifying CPTs.